Correlation of antigen-specific immune response with disease severity among COVID-19 patients in Bangladesh - Bhuiyan, Taufiqur Rahman; Al Banna, Hasan; Kaisar, M. Hasanul; Karmakar, Polash Chandra; Hakim, Al; Akter, Afroza; Ahmed, Tasnuva; Tauheed, Imam; Islam, Shaumik; Hasnat, Mohammad Abul; Sumon, Mostafa Aziz; Rashed, Asif; et al. (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) is a protean disease causing different degrees of clinical severity including fatality. In addition to humoral immunity, antigen-specific T cells may play a critical role in defining the protective immune response against SARS-CoV-2, the virus that causes this disease. As a part of a longitudinal cohort study in Bangladesh to investigate B and T cell-specific immune responses, we sought to evaluate the activation-induced marker (AIM) and the status of different immune cell subsets during a COVID-19 infection. We analyzed a total of 115 participants, which included participants with asymptomatic, mild, moderate, and severe clinical symptoms. We observed decreased mucosal-associated invariant T (MAIT) cell frequency on the initial days of the COVID-19 infection in symptomatic patients compared to asymptomatic patients. However, natural killer (NK) cells were found to be elevated in symptomatic patients just after the onset of the disease compared to both asymptomatic patients and healthy individuals. Moreover, we found a significant increase of AIM+ (both OX40+CD137+ and OX40+CD40L+) CD4+ T cells in moderate and severe COVID-19 patients in response to SARS-CoV-2 peptides (especially spike peptides) compared to pre-pandemic controls who are unexposed to SARS-CoV-2. Notably, we did not observe any significant difference in the CD8+ AIMs (CD137+CD69+), which indicates the exhaustion of CD8+ T cells during a COVID-19 infection. These findings suggest that patients who recovered from moderate and severe COVID-19 were able to mount a strong CD4+ T-cell response against shared viral determinants that ultimately induced T cells to mount further immune responses to SARS-CoV-2.